Tablet-Administered Screening Tests for the Detection of Major and Mild Cognitive Disorders – Preliminary Findings of a Comparative Study - Solias, Andreas; Chaldogeridis, Agisilaos; Batzikosta, Areti; Tsolaki, Magdalini (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Preventative screening of at-risk population is a crucial step in the early detection of dementia. Building alternative and ecologically validated screening tests are challenging. This pilot project attempts a) to assess the effectiveness of a culturally oriented computerized screening test for major neurocognitive disorder (eHAST) b) to compare it with the Greek version of the UCSF Brain Health Assessment (BHA) which is culturally neutral. Our study focused in a) evaluation of eHAST’s discriminant ability between groups of older adults with cognitive concerns (OACC) (n=35) vs older adults with Mild Cognitive Impairment (MCI) (n=114) and dementia (n=67), and MCI vs dementia in a sample of 216 cases. b) comparison of eHAST’s discriminant ability vs BHA’s in 116 subjects. The absence of normative data for both of the tests led to balance the sample regarding age and educational level for the comparisons between groups of OACC vs MCI (n = 56) and MCI vs dementia cases (n = 60). All participants were neuropsychologically assessed, clinically diagnosed. Results showed a) Reliability check (Cronbach’s alpha) of eHAST was 0.9 and discriminant analyses in separating groups of OACC vs MCI displayed a correct classification rate of 77.3%, for MCI vs dementia 80.6% and OACC vs dementia 89.1% (cross-validated). b) In OACC vs MCI comparison, BHA’s discriminant ability was 67.3% and eHAST’s was 60.7%. In MCI vs dementia comparison, BHA’s discriminant ability was 77.2% and eHAST’s was 76.7% (cross-validated). These preliminary results of the implementation of eHAST are encouraging as the test presents sufficient discriminant ability between groups of OACC-MCI, MCI-Dementia & OACC- Dementia. Also, performs similar scores to BHA, which is a state-of-the-art screening test. The use of a tablet pc in the assessment of cognitive disorders in the elderly can have a catalytic role in the detection of dementia.